Do Obese Women Receive the Necessary Interventions to Achieve Vaginal Birth after Cesarean? - Faucett, Allison M.; Allshouse, Amanda A.; Donnelly, Meghan; Metz, Torri D. (American Journal of Perinatology, 2016)
Objective We aimed to determine if obese women undergoing trial of labor after cesarean (TOLAC) were more likely to undergo repeat cesarean for arrest disorders prior to active labor, and whether this was due to decreased use of standard interventions to achieve vaginal birth.Study Design This was a secondary analysis of a prospective registry. Women undergoing TOLAC with one prior cesarean and a singleton, term gestation who had a repeat cesarean for an arrest disorder were included. The primary outcome was repeat cesarean prior to active labor (cervical dilation < 6 cm). Obese (body mass index ≥30 kg/m2) and nonobese women were compared. Multivariable logistic regression was used to estimate the association between obesity and repeat cesarean prior to active labor. Clinical interventions were compared between groups using t-test and χ2 test.Results Among 2,098 women undergoing TOLAC, 1,454 (69%) were obese. Obese women were more likely to undergo repeat cesarean for an arrest disorder prior to active labor (odds ratio, 1.4; 95% confidence interval, 1.1–1.7) despite being allowed longer labors and receiving higher maximum doses of oxytocin for a longer duration than nonobese women.Conclusion Obese women were more likely to undergo repeat cesarean prior to active labor despite more clinical interventions to achieve vaginal birth.
Keywords: arrest disorder; obesity; trial of labor after cesarean; vaginal birth after cesarean